Unexpected Enhancement of HDACs Inhibition by MeS Substitution at C-2 Position of Fluoro Largazole - Bingbing Zhang; Zhu-Wei Ruan; Dongdong Luo; Yueyue Zhu; Tingbo Ding; Qiang Sui; Xinsheng Lei (Marine Drugs, 2020)
Given our previous finding that fluorination at the C18 position of largazole showed reasonably good tolerance towards inhibitory activity and selectivity of histone deacetylases (HDACs), further modification on the valine residue in the fluoro-largazole’s macrocyclic moiety with S-Me l-Cysteine or Glycine residue was performed. While the Glycine-modified fluoro analog showed poor activity, the S-Me l-Cysteine-modified analog emerged to be a very potent HDAC inhibitor. Unlike all previously reported C2-modified compounds in the largazole family (including our recent fluoro-largazole analogs) where replacement of the Val residue has failed to provide any potency improvement, the S-Me l-Cysteine-modified analog displayed significantly enhanced (five–nine-fold) inhibition of all the tested HDACs while maintaining the selectivity of HDAC1 over HDAC6, as compared to largazole thiol. A molecular modeling study provided rational explanation and structural evidence for the enhanced inhibitory activity. This new finding will aid the design of novel potent HDAC inhibitors.